Forced Sterilizations in Slovakia: Twenty Years of Courge and Engagement of Romani Women - Ivanco, Štefan (Romano džaniben, 2019)
The article analyzes the historical development and current state of research on forced sterilizations of Roma women in the former Czechoslovakia and its successor states. It deals with an issue that has long been marginalized in public and professional discourse and shows how the issue of sterilization has changed from the communist regime to the current efforts to document, reflect on, and legally settle these practices. The author clearly summarizes the main findings of historiography, professional approaches, and the international context, and also pays attention to how the experiences of Roma women have been captured in the public sphere and in research works. The result is a comprehensive view of the unique interconnection of historical sources, social consequences, and ethical aspects of the issue under investigation.